2020
DOI: 10.4018/jeco.2020010102
|View full text |Cite
|
Sign up to set email alerts
|

Investigating B-to-B Social Media Implementation

Abstract: Social media usage keeps exploding all over the world which makes it an incrementally important resource to be more competitive in both business-to-customer and business-to-business marketing. However, even though social media has been widely used in B-to-B, previous researches still claim that B-to-B marketers are far behind B-to-C marketers either in the level of use or in the sophistication for social media. Building on the electronic marketing orientation (EMO) proposition and media richness theory, this r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…Although this path has not been studied in prior research studies, this result agrees with other studies that have tested the impact of similar concepts on perceived value in the context of financial services and FinTech. Indeed, prior studies have suggested that convenience and efficiency are among the principal relative advantages of new technologies and services (Lin and Lu 2015 ; Nel and Heyns 2017 ), having been studied as determinants of utilitarian values (Lin and Lu 2015 ; Wang 2022 ). More specifically, Wang ( 2022 ) verified the impact of relative advantage on the utilitarian and hedonic dimensions of perceived value within the context of mobile payment.…”
Section: Discussionmentioning
confidence: 99%
“…Although this path has not been studied in prior research studies, this result agrees with other studies that have tested the impact of similar concepts on perceived value in the context of financial services and FinTech. Indeed, prior studies have suggested that convenience and efficiency are among the principal relative advantages of new technologies and services (Lin and Lu 2015 ; Nel and Heyns 2017 ), having been studied as determinants of utilitarian values (Lin and Lu 2015 ; Wang 2022 ). More specifically, Wang ( 2022 ) verified the impact of relative advantage on the utilitarian and hedonic dimensions of perceived value within the context of mobile payment.…”
Section: Discussionmentioning
confidence: 99%